2019
DOI: 10.5455/medarh.2019.73.195-200
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic, Bone Densitometry and Clinic Outcomes Assessments in Femoral Shaft Fractures Fixed by Plating or Locking Retrograde Nail

Abstract: Introduction: Distal femoral shaft fractures are characterized by increasing incidence and complexity and are still considered a challenging problem (high morbidity and mortality). No consensus on best surgical option has been achieved. Aim: This study aims is to investigate radiographic, mineral bone densitometry and clinical outcomes of locking retrograde intramedullary (LRN) nailing and anatomical locking plate to surgically treat distal femoral shaft fractures in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…However, consensus about the best management option remains controversial. Rollo et al reported no statistical difference for the use of locking retrograde IMN or plate in terms of surgery time, blood transfusion, and wound healing [ 9 ]. In contrast, IMN has been reported as significantly favorable for a patient’s post-operative quality-of-life [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, consensus about the best management option remains controversial. Rollo et al reported no statistical difference for the use of locking retrograde IMN or plate in terms of surgery time, blood transfusion, and wound healing [ 9 ]. In contrast, IMN has been reported as significantly favorable for a patient’s post-operative quality-of-life [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the external rotation, abduction, and flexion displacement of the proximal fragment in subtrochanteric fractures, it is difficult to achieve reduction using this technique alone, and the use of a second reduction tool, such as a ball spike, the Schanz pin and a periosteal elevator, may be necessary. We did not apply this technique to retrograde nail because the tension resulting from the traction play a very important role in our reduction process, and the reduction is always achieved by flexing the knee to reduce the muscle force in the retrograde nail fixation process [24]. Heterotopic ossification was observed during the follow-up period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, utilization of retrograde femoral nailing has gained popularity and has become widely accepted. 29 , 30 , 31 …”
Section: Antegrade Femoral Nailingmentioning
confidence: 99%